Adakites and associated granitoids from the Serra da Prata Arc: Evidence for a Tonian subduction setting within the Araçuaí-Ribeira orogenic system (AROS), SE Brazil. (November 2021) - Decol, Joventine; Heilbron, Monica; Peixoto, Caroline; Bruno, Henrique; Bersan, Samuel Moreira; Rodrigues, Sergio Wilians de Oliveira; Corrales, Felipe; Eirado, Luiz Guilherme; Tupinambá, Miguel
Abstract: Within deeply eroded orogenic belts, the geochemical signatures of metamorphosed igneous rocks can be used to constrain modern-like tectonic models operating in Precambrian times. One important aspect of this discussion is the presence or not of pre-collisional arc-related rocks that would represent the magmatic product of subduction processes imprinted on the upper plate of the convergent setting. New detailed geological and geochemical data of the northern segment of the Tonian to Cryogenian juvenile Outer Arc of the Araçuaí-Ribeira Orogenic System (AROS) are presented. Results were combined with recently published U–Pb and Hf data to contribute to a comprehensive tectonic model. The arc-related rocks (Serra da Prata Complex), transformed in foliated orthogneisses, are interlayered with dolomitic marbles, amphibolites, and psammo-pelitic paragneisses (Italva Group). This association is similar to the one described in the southern part of the orogenic system, pointing to the extension of the Outer Arc system until the Rio Doce River, in the transition zone between the Araçuaí and Ribeira segments of the AROS. New geochemical analyses together with reinterpreted published data indicate the presence of typical adakites that, together with normal calc-alkaline expanded series, island arc tholeiitic series, and A-type granitoids, corroborate with a modern style plate tectonic model. The envisaged model started in the Tonian, with E-verging subduction that resulted in the production of very juvenile arc-related rocks and associated fore-to back-arc basins filled with carbonatic rocks, meta-volcanic rocks, and MORB-like basaltic rocks. The typical adakites are considered the result of partial melting of young and hot oceanic lithosphere under moderate to high pressures in which garnet was an important stable residue. Potassic C-type adakitic rocks formed by the partial melting of thickened lower crust occur associated with the typical adakites. The occurrence of both adakites, together with A-type granitoids, characteristic of the investigated terminal sector of the Serra da Prata arc, is interpreted to result from a slab window gap, either associated with slab tearing/ridge subduction or slab roll-back, hampering an intracontinental model for the Ribeira orogen. Graphical abstract: Image 1 Highlights: First description of adakite within the Tonian pre-collisional rocks of the external Magmatic Arc. A-Type granite, Adakite and OIB suggests a slab window during subduction processes. The available data reinforces subduction-related scenario for the Serra da Prata stage of the External Magmatic Arc.